2014
DOI: 10.1111/hae.12379
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the experience of caring for children with haemophilia: cross‐sectional study of caregivers in the United States

Abstract: Congenital haemophilia is an inherited bleeding disorder typically diagnosed at birth or shortly thereafter. Haemophilia imposes a significant burden on patients and their caregivers. The aim of the study was to quantify the overall burden of haemophilia on caregivers in the USA using a novel disease-specific questionnaire and the previously validated CarerQol. Targeted literature review and a previous survey conducted by the authors was used to develop an online questionnaire with six burden domains of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 24 publications
8
45
0
3
Order By: Relevance
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The strong association between inhibitor development and increased perceived burden for parents of children with haemophilia is not unexpected, and this result is consistent with previous research (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ; DeKoven et al, ; Lindvall et al, ; Ljung et al, ). Given this, the HCP must recognise and provide sufficient support to parents of children with inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…A cross‐sectional, international study using a generic instrument showed that parents of children with inhibitors reported a higher impact of the illness than parents of children without inhibitors (Lindvall et al, ). Lindvall’s et al () results are in line with two studies using an online questionnaire to identify areas of burden among parents of children with haemophilia (DeKoven, Karkare, Kelley, et al, ; DeKoven, Karkare, Lee, et al, ).…”
Section: Introductionsupporting
confidence: 68%
“…Haemophilia, treatment complications, inhibitors, pain and arthropathy can impact patients psychologically (stress and coping, anxiety and depression, stigmatization and discrimination) and economically . This impacts not only on the health‐related quality of life (HRQoL) of haemophilia patients, but also their caregivers . Khair et al also described that haemophilia has an economic impact on caregivers’ HRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…When a child is initially diagnosed, shock, denial, anger and depression are common emotional responses of the parents [79] that play a significant role in the care of a child with hemophilia and refers to experiencing a large responsibility for management of hemophilia at home [80]. Parents have to face not only feelings of anxiety, guilt and worry over their child’s condition, but also the impact of pain during infusion [81].…”
Section: Psychological Issuesmentioning
confidence: 99%